INCLUSION OF PEOPLE WITH VISUAL DISABILITIES:: AN ANALYSIS OF BRAZILIAN LEGISLATION AND ITS CHALLENGES (REMUNOM, 2024)
This article addresses the social inclusion of visually impaired people in the Brazilian context, examining the legal bases that support equal opportunities, access to education and work, and active participation in society based on the Federal Constitution of 1988, Brazilian Law for the Inclusion of People with Disabilities, the Accessibility Law and the Quota Law. Pertinent subjects such as inclusive education, accessibility, prejudice in society and the challenges faced in the implementation of these measures and the prospects for a more inclusive future are also addressed and discussed.